EFEKTIVITAS PRENATAL YOGA DALAM MENGURANGI ANGKA KEJADIAN PRE EKLAMPSIA DI PMB TATI KUSMIRAN,S.Tr.KEB.,BD BEKASI TAHUN 2023 - Ekayanti, Ekayanti; Swandayani, Rasta (Bina Generasi : Jurnal Kesehatan, 2024)
The three main causes of maternal death include bleeding (30%), hypertension in pregnancy or preeclampsia (25%), and infection (12%). Preeclampsia or eclampsia is the second most common cause of maternal death after bleeding. Exercise during pregnancy can increase stamina, make you sleep better, improve your mood, and reduce anxiety. Of this writing is to determine the effectiveness of prenatal yoga in reducing the incidence of pre-eclampsia in PMB Tati Kusmiran, S.Tr.Keb., BD Bekasi in 2023. This research design uses a true-experimental research design which is a Posttest-only control design, namely an experimental design using a sample to measure the frequency of the effectiveness of prenatal yoga in reducing the incidence of pre-eclampsia in PMB Tati Kusmiran, S.Tr.Keb., BD Bekasi, Identifying the effectiveness of prenatal yoga on the incidence of pre-eclampsia in pregnant women by carrying out interventions. There were differences between groups experiencing pre-eclampsia in the BP category <140/90 with a frequency of 69.2% and those who did not comply with the SOP had a frequency of 30.8%. 35.3% of those who experienced pre-eclampsia in the BP>160/110 category did prenatal yoga according to the SOP and 64.7% of those who did not according to the SOP. There is a difference in the mean scores for the two groups with a score difference of 0.47. Based on the results of the paired test, the value p = obtained p = 0.000 < 0.01, so H0 is rejected, meaning that statistically it shows that there is a difference in pre-eclampsia in pregnant women who do yoga according to the SOP and those who do yoga not according to the SOP. Based on the results of the paired test, the p= value was obtained, the p=0.000 <0.01 was obtained, so H0 was rejected, meaning that statistically it shows that there is a difference in pre-eclampsia in pregnant women who do yoga according to the SOP and those who do yoga not according to the SOP. The results of the normality test using the Shapiro Wilk test obtained a sig value. 0.000, which means that if the α value <0.05, it means Ho is rejected and it can be concluded that there is the effectiveness of prenatal yoga in reducing the incidence of pre-eclampsia in PMB Tati Kusmiran, S.Tr.Keb., BD Bekasi